Zero Index Metamaterial for Designing High-Gain Patch Antenna - Yahong Liu; Xiaojing Guo; Shuai Gu; Xiaopeng Zhao (International Journal of Antennas and Propagation)
A planar wideband zero-index metamaterial (ZIM) based on mesh grid structure is studied. It is demonstrated that the real part of the index approaches zero at the wideband covering from 9.9 GHz to 11.4 GHz. Two conventional patch antennas whose operating frequencies are both in the range of zero-index frequencies are designed and fabricated. And then, the ZIM is placed in the presence of the conventional patch antennas to form the proposed antennas. The distance between the antenna and the ZIM cover is investigated. Antenna performances are studied with simulations and measurements. The results show that the more directional and higher gain patch antennas can be obtained. The measured results are in good agreement with the simulations. Compared to the conventional patch antenna without the ZIM, it is shown that the beamwidth of antenna with the ZIM cover becomes more convergent and the gain is much higher.